2018
DOI: 10.1017/jfm.2018.474
|View full text |Cite
|
Sign up to set email alerts
|

The role of the seam in the swing of a cricket ball

Abstract: The role of the seam in the ‘swing’ of a cricket ball is investigated via unsteady force and surface-pressure measurements and oil-flow visualization in a low-turbulence wind tunnel. Various seam angles of the ball and flow speeds are considered. Static tests are carried out on a new ‘SG Test’ cricket ball as well as its idealized models: a smooth sphere with one and five trips. To study the effect of surface roughness of the ball as the game progresses, force measurements are also carried out on a cricket bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(96 citation statements)
references
References 18 publications
20
64
0
Order By: Relevance
“…A top-class fast bowler typically releases the ball between 80 and 90 mile/h. A simple one-dimensional numerical solution of the trajectory based on a drag coefficient of 0.5 (measurements of drag were made as part of this study but not presented here; however, this is consistent with Deshpande et al 13 ) shows that the ball will slow by approximately 15% from the point of release to reaching the stumps. At a bowling speed of 85 mile/h out of the hand, the ball will therefore slow to 72 mile/h by the time it reaches the batsman.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A top-class fast bowler typically releases the ball between 80 and 90 mile/h. A simple one-dimensional numerical solution of the trajectory based on a drag coefficient of 0.5 (measurements of drag were made as part of this study but not presented here; however, this is consistent with Deshpande et al 13 ) shows that the ball will slow by approximately 15% from the point of release to reaching the stumps. At a bowling speed of 85 mile/h out of the hand, the ball will therefore slow to 72 mile/h by the time it reaches the batsman.…”
Section: Resultssupporting
confidence: 88%
“…From a fluid-dynamic perspective, Scobie et al 10 were the first to postulate and experimentally observe that the reversed asymmetric pressure force driving RS is due to a laminar separation bubble (LSB) on the non-seam side of the ball. This has been recently verified by Deshpande et al 13 The LSB for RS is illustrated schematically in Figure 3. There is turbulent separation on the seam side as before due to prominent primary seam.…”
Section: Literature Review Of the Fluid Dynamics Of Swingsupporting
confidence: 70%
See 1 more Smart Citation
“…The presence of the LSB on a non-rotating cricket ball was first demonstrated by Scobie et al [5] and later validated by Deshpande et al [14]. Scobie et al demonstrated this phenomenon using heated flow visualization and pressure measurements on both a double-scaled ball and on actual cricket balls aged under first-class match conditions.…”
Section: Flow Separation On Spheres and Cricket Ballsmentioning
confidence: 92%
“…Figure 4. Evidence of a laminar separation bubble on the NSS using two different methods: (a) heat flow method on a double-sized cricket ball model[5] and (b) oil flow visualization on a sphere with a trip[14].…”
mentioning
confidence: 99%